MAGNETIC SUSCEPTIBILITIES DISTRIBUTION AND ITS POSSIBLY GEOLOGICAL SIGNIFICANCE OF SUBMERGED BELITUNG GRANITE - DIDA KUSNIDA; P. Astjario Astjario; B. Nirwana (Indonesian Mining Journal, 2008)
An appraisal of the marine magnetic anomalies over the Belitung water provides information on the distribution of the magnetic susceptibility values. The 0.001 to 0.003 cgs unit contour values charac- terize the zone of submerged Belitung granite coincides with the zone of less than 50 nT total mag- netic anomaly contour value. Susceptibilities distribution analyses reveal a strong correlation between magnetic susceptibility and type of granites. The nature of submerged Belitung intrusive is suggested to be granitic pluton of biotite-granite that is associated with cassiterite minerals.